Quality assessment of private practitioners in rural Wardha, Maharashtra - Ganguly Enakshi; Deshmukh P; Garg B (Wolters Kluwer Medknow Publications, 2008)
Objective: To assess the quality of care provided by private practitioners in rural areas of Wardha district. Methodology: The study was carried out in three primary health centres of Wardha district. 20% of the 44 registered private practitioners were selected randomly for the study. The data was collected using checklist through direct observation for the infrastructure. Assessment of quality of services delivered, 10 consecutive patients were observed and also the medical practitioner was interviewed. Supplies and logistics were assessed through observation. Results: All the facilities were sheltered from weather conditions and 90% had adequate waiting space. But, drinking water and adequate IEC material was available in only 20% facilities. Complete history taking and relevant physical examination was done in only 20% cases. Only 20% practitioners recorded blood pressure and 30% recorded temperature in cases with fever. Provisional diagnosis was not written in any of the case and only 20% explained prescription to the patients. Conclusion: There is considerable scope to improve the quality of services of private practitioners. To achieve this quality assurance programs may be initiated along with the training of private medical practitioners.